Prevalence of UDP-glucuronosyltransferase polymorphisms (UGT1A6∗2, 1A7∗12, 1A8∗3, 1A9∗3, 2B7∗2, and 2B15∗2) in a - Khalid M. Alkharfy; Basit L. Jan; Sibtain Afzal; Fahad I. Al-Jenoobi; Abdullah M. Al-Mohizea; Saleh Al-Muhsen; Rabih Halwani; Mohammad K. Parvez; Mohammed S. Al-Dosari (Elsevier, 2017)
Glucuronidation is an important phase II pathway responsible for many endogenous substances and drug metabolism. The present work evaluated allele frequencies of certain UDP-glucuronosyl-transferases (UGT 1A6∗2, A7∗12, A8∗3, A9∗3, 2B7∗2, and 2B15∗2) in Saudi Arabians that could provide essential ethnic information. Blood samples from 192 healthy unrelated Saudi males of various geographic regions were collected. Genomic DNA was isolated and genotyping of various UGTs was carried out using polymerase chain reaction (PCR) followed by direct sequencing. For UGT1A6∗2 A/G genotype, the most common variant was the homozygous repeat (AA) and the most common allele was (A) with a frequency of 46.5% and 67.3%, respectively. Similarly, the most common variant for UGT1A7∗12 T/C genotype was the heterozygous repeat (TC) with a frequency of 78.7% while the mutant allele (C) was present in 60.6% of the study population. Both UGT1A8∗3 (G/A) and UGT1A9∗3 (T/C) showed only a wild homozygous pattern in all screened subjects. For UGT2B7∗2, the heterozygous repeat (TC) was found with a frequency of 57.3% and the alleles (A) showed a frequency of 50.8%. In contrast, for UGT2B15∗2 (G253T), the heterozygous repeat (TG) presented 62.3% of the subjects where the most common allele (G) was with a frequency of 66.2%. In conclusion, our data indicate that Saudis harbor some important UGT mutations known to affect enzyme activity. Additional studies are therefore, warranted to assess the clinical implications of these gene polymorphisms in this ethnic group.